A high unburned carbon fly ash concrete’s performance characteristics (2011)
Engineering today requires that structures are strong and durable; the latter concept is a decisive factor in their design and construction. The scientific community continues developing new cementitious materials and improving tra-ditional concrete’s properties, specifically reducing permeability by incorporating materials such as pozzolans. This paper analyses the effect of fly ash (FA) added to concrete on mechanical strength regarding compression, capillary absorption and chloride permeability and their behaviour compared to concrete containing silica fume (SF). An optimum 10% mechanical strength was found for fly ash; however, this increased with addition, resulting in positive effects on durability. Fly ash had lower performance for all properties evaluated when compared to silica fume.